Influence of media constitutions on the biosynthesis of cephalosporin C. - Chakraborty, Tanushree (Recent Research in Science and Technology, 2013)
Cephalosporin acremonium was used for the production of cephalosporin C in batch mode of cultivation. The Cephalosporin is a ï¢ lactam antibiotic that has the ability to kill gram positive as well as gram negative bacteria by destroying their peptidoglycan layer of cell wall. There are four generations of cephalosporin depending upon the ability to kill gram positive, gram negative bacteria or both the type of bacteria. The effect of different medium constituents for better yield of cephalosporin C was thoroughly studied. From the results of fermentation it was found that sucrose as carbon source, soya bean meal as nitrogen source, 6.8 pH, RT and 96 hrs of incubation are most suitable for higher yield of antibiotic.